Vagus Nerve Cross-Sectional Area in Patients With Parkinson's Disease—An Ultrasound Case-Control Study - Horsager, Jacob; Walter, Uwe; Fedorova, Tatyana D.; Andersen, Katrine B.; Skjærbæk, Casper; Knudsen, Karoline; Okkels, Niels; von Weitzel-Mudersbach, Paul; Dyrskog, Stig Eric; Bergholt, Bo; Borghammer, Per (Frontiers in Neurology, 2021)
Background. Vagal parasympathetic neurons are prone to degeneration in Parkinsons disease (PD). High-resolution ultrasound can precisely estimate the cross-sectional area (CSA) of peripheral nerves. Here, we tested the hypothesis that vagus CSA is reduced in PD. Methods. We included 56 healthy controls (HCs) and 63 patients with PD. Using a high-end ultrasound system equipped with a high-frequency transducer, five images were obtained of each nerve. The hypoechoic neuronal tissue was delineated offline with dedicated software and the CSA extracted. Results. In the initial PD vs. HC comparison, no statistically significant differences were observed in mean left vagus CSA (HC: 1.97mm2, PD: 1.89mm2, P=0.36) or in mean right vagus CSA (HC: 2.37mm2, PD: 2.23mm2, P=0.17). The right vagus CSA was significantly larger than the left vagus CSA in both groups (P<0.0001). Females were overrepresented in the HC group and presented with generally smaller vagus CSAs. Consequently, sex-adjusted CSA was significantly smaller for the right vagus nerve of the PD group (P=0.041), but not for the left. Conclusion. A small but significant reduction in sex-adjusted right vagus CSA was observed in patients with PD. The left vagus CSA was not significantly reduced in patients with PD. Ultrasound may not be a suitable method to detecting vagal axonal loss in individual patients.